When Will Christ Come Again?. (1st March 2021) - Eagleton, Terry
Abstract: This essay considers possible answers to the question, 'When will Christ come again?', and argues that the Second Coming is most intelligible not as an arbitrary arrest of history but as an act of mercy in circumstances which cry out for it.